The Preclinical Evidence for Peltophorum Pterocarpum Extracts And Pure Compound In Pain And Inflammation Models Along With In-Vitro Antioxidant And Acute Toxicity Assessment To Validate Its Traditional Uses. - Farhana Tasleem; Abdullah Hadi; Marium Tariq; Sana Ejaz; Asma Irshad; Ali Asgher Shuja (Kurdish Studies, 2024)
Peltophorum pterocarpum, a medicinal plant known for its analgesic, anti-inflammatory and antioxidant properties, was studied for the pharmacological effects and toxicity of its ethanol and hexane leaves extracts, focusing on the isolated compound bergenin. Bergenin was extracted using methanol and assessed for antioxidant activity using the FRAP assay. In vivo tests in rodents showed significant analgesic and anti-inflammatory effects without toxicity at tested doses. The hexane extract and bergenin exhibited strong dose-dependent responses. Findings confirm the plant’s traditional uses and identify bergenin as a safe, promising candidate for development as a natural analgesic and anti-inflammatory agent.